Relationship between perfectionism and marital satisfaction among graduate students - Mee, Foo Fatt; Hassan, Siti Aishah; Baba, Maznah; Talib, Mansor Abu; Zakaria, Noor Syamilah (Contemporary Research Center, 2015)
This study aimed to examine the relationship between self-perfectionism, dyadic perfectionism, and marital satisfaction among graduate students. Respondents were recruited based on purposive sampling. A total of 30 graduate students participated in the study. The result shows that dyadic perfectionism is significantly correlated with marital satisfaction in a negative direction. Respondents who hold high standard and high discrepancy to their partner tend to be less satisfied in their marriage. Implication to counselling service is discussed.